A modular theranostic platform for tumor therapy and its metabolic studies. Issue 17 (27th March 2019) - Li, Ke; Li, Jiang-Lan; Zheng, Di-Wei; Zeng, Xuan; Liu, Chuan-Jun; Zhang, Xian-Zheng
Abstract : A novel nanoplatform with pH stimulating benzimidazole and glutathione stimulating ferrocene as stoppers was fabricated. The nanoplatform could be modularized to construct carriers with remarkable theranostic and synergistic antitumor properties. Abstract : Theranostic systems are able to detect and treat diseases with only one procedure, thus greatly lessening the pain of patients. Since each patient's disease can be considered as a new clinical subtype, it is essential to develop theranostic nanomaterials with changeable functions for personal treatment. In this work, a novel modular theranostic platform was designed to control the stimuli-responsive drug release. As a patch board, mesoporous silica nanoparticles (MSNs) were functionalized with a linear pH-responsive benzimidazole (Bz)-polyethylene glycol (PEG) chain containing a redox-responsive ferrocene (Fc) oxide stopper at the end. As the plug, the β-CD ring was initially located at the Bz position. In an acidic tumor microenvironment, the pH sensitive Bz was protonated and the complex formation constant between Bz and β-CD decreased. At the same time, the complex formation constant between Fc and β-CD increased remarkably. As a result, the β-CD ring would depart from the nanoparticle surface to the Fc position at pH 6.2 & 10 mM GSH, physically causing an "And" logic gate type drug release. Herein, a "plug and play" method was used to achieve changeable functions with only one platform. By plugging modified β-CD into the patch board, theranostic systems with changeable functions can be achieved easily.